2013
DOI: 10.37190/epe130409
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of bioaerosols in the air around the facilities of waste collection and disposal

Abstract: Exposure to bioaerosols at various stages of waste management system (collection, transfer and disposal) has been evaluated by recording of the bacterial and fungal concentrations in the air around these facilities. Regardless of the season, the total bacteria and total fungi were detected for all samples, whereas the fungal genera were not. The bioaerosol concentrations measured in the waste collection bins were significantly higher than those of the transfer station and landfill site. The mean microbial conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…Huang et al [38] also documented the higher microbial concentration in the wet season as compared to other seasons. In contrast to bacteria, the highest fungal concentration was recorded in the dry season than wet season and this corresponds to the results of other researchers [9,39]. In previous studies, the highest concentration of bioaerosol was found in the air samples of wastewater treatment facilities during summer and autumn seasons than that of spring and winter seasons because of small rainfall and suitable temperature [40,41].…”
Section: Resultssupporting
confidence: 89%
“…Huang et al [38] also documented the higher microbial concentration in the wet season as compared to other seasons. In contrast to bacteria, the highest fungal concentration was recorded in the dry season than wet season and this corresponds to the results of other researchers [9,39]. In previous studies, the highest concentration of bioaerosol was found in the air samples of wastewater treatment facilities during summer and autumn seasons than that of spring and winter seasons because of small rainfall and suitable temperature [40,41].…”
Section: Resultssupporting
confidence: 89%
“…Whilst some work has been undertaken to assess the health risks associated with bioaerosols emitted from general waste collection (Neumann et al, 2005, Roodbari et al, 2013, Kuijer et al, 2010, Neumann et al, 2014, Schantora et al, 2015, source separated recyclable collection (Heldal et al, 1997) and indoor storage of organic waste (Wouters et al, 2000) no studies to date have detailed the risks associated with storage and collection of containers (bins) containing only the residual fraction after recycling. Therefore, the aims of this study were three-fold: 1) To explore the potential for bioaerosol emissions arising from the extended storage of residual waste material, 2) To explore the link between these emissions and potential health impacts on householders and waste collectors, and,…”
Section: Introductionmentioning
confidence: 99%
“…100 μm, with the size of virus particles serving as the lower limit and structures of pollen or seeds being the upper limit. The problem of bioaerosols concerns several scientific fields, beginning with medicine, through botany, zoology, environmental engineering, and ecology and ending with typical microbiology (Roodbari et al 2013 ; O’Connor et al 2015 ). The studies conducted in Poland and throughout the world are focused on, e.g., the mechanisms of bioaerosol formation (Mandal and Brandl 2011 ; Tomasi and Lupi 2017 ; Blanchard and Syzdek 1970 ), bioaerosol content (Fuzzi et al 2006 ; Tomasi and Lupi 2017 ), methods of sampling air for studies (Pastuszka et al 2013 ; Gregová et al 2008 ), and abundance and type of microorganisms in the indoor and outdoor environment as well as the influence of different objects on the air contamination level (Mentese and Tasdibi 2016 ; Dungan 2012 ; Wéry 2014 ; Górny and Dutkiewicz 2002 ).…”
Section: Introductionmentioning
confidence: 99%
“…Municipal wastewater which enters the WWTP contains numerous pathogenic microorganisms which may form bioaerosols and be lifted into atmospheric air as a result of flow, turbulence, and aeration of wastewater (Carducci et al 2000 ; Thorn et al 2002 ; Maki et al 2017 ). Moreover, side-products such as screenings, sand, or sewage sludge formed during subsequent stages of treatment also contain hazardous, often pathogenic microorganisms which may have a negative impact on the environment, WWTP employees, and the inhabitants of local areas (Uhrbrand et al 2011 ; Pringle 2013 ; Roodbari et al 2013 ).…”
Section: Introductionmentioning
confidence: 99%